Association Between Informal Caregiving and Changes in Cardiovascular-related Health Behaviors Among Middle-aged and Older Adults in Japan: A 15-year Panel Survey - Yuta Taniguchi; Atsushi Miyawaki; Masao Iwagami; Takehiro Sugiyama; Taeko Watanabe; Tomoko Ito; Nanako Tamiya (Journal of Epidemiology)
Background: Studies have shown that informal caregiving is associated with an increased risk of cardiovascular diseases. However, there is limited evidence on the mechanisms involved. To fill this knowledge gap, we investigated the association of informal caregiving with changes in health-related behaviors. Methods: We analyzed a nationally representative sample aged 50–59 years as of 2005 using fifteen waves of the Longitudinal Survey of Middle-Aged and Older Adults, which was conducted between 2005–2019. We investigated the association between the change in informal caregiving status and the change in health-related behaviors, including (1) heavy drinking, (2) smoking, (3) no exercise habits, and (4) no attendance at annual health checkups. We used multivariable logistic regression models with correlated random effects, adjusting for individual-level time-invariant characteristics. Results: Among 268,165 observations from 30,530 participants (median age 55; interquartile range, 52–57 years at baseline; 51.6% women), 32,164 (12.0%) observations from 10,224 individuals provided informal care. After adjusting for potential confounders, informal caregiving was associated with higher probabilities of deteriorating health-related behaviors, including heavy drinking (adjusted odds ratio [aOR] 1.16; 95% confidence interval [CI], 1.03–1.32; adjusted P = 0.032) and no exercise habits (aOR 1.09; 95% CI, 1.04–1.15; adjusted P < 0.001). We observed similar patterns for smoking (aOR 1.12; 95% CI, 1.001–1.26; adjusted P = 0.053) and no attendance at health checkups (aOR 1.05; 95% CI, 0.999–1.10; adjusted P = 0.053). Conclusion: This study showed that the transition into informal caregiving was associated with deteriorating cardiovascular-related health behaviors in Japan. These findings highlighted the importance of continued efforts to prevent the deterioration of caregivers’ health-related behaviors.